Yokukansan Inhibits the Development of Morphine Tolerance by Regulating Presynaptic Proteins in DRG Neurons - Ohashi, Yusuke; Sakhri, Fatma Zahra; Ikemoto, Hideshi; Okumo, Takayuki; Adachi, Naoki; Sunagawa, Masataka (Frontiers in Pharmacology, 2022)
Abstract Opioids, such as morphine, are used in the clinical settings for the management of acute and chronic pain. However, long-term use of morphine leads to antinociceptive tolerance and hypersensitivity. The cellular and molecular mechanisms of morphine tolerance seem to be quite complex, with suggestions including internalization of the μ-opioid receptor (MOR), neuroinflammation with activation of microglia and astrocytes, and changes in synaptic function in the central nervous system. Yokukansan (YKS), a traditional Kampo medicine consisting of seven herbs, has been used to treat emotional instability, neurosis, and insomnia. Interestingly, recent studies have begun to reveal the inhibitory effect of YKS on the development of morphine tolerance. In the present study, we determined the effect of YKS on morphine tolerance formation and its mechanisms in a rat model, focusing on the synapses between primary sensory neurons and spinal dorsal horn secondary neurons. We found that morphine tolerance formation was significantly inhibited by YKS (0.3 or 1.0 g/kg/day) preadministration for 7 days. Repeated administration of morphine (10 mg/kg/day) increased the expression of presynaptic proteins, including synaptotagmin I, in the spinal cord, which was suppressed by YKS. Furthermore, these changes in presynaptic protein expression were more pronounced at isolectin B4 (IB4)-positive excitatory synapses around the lamina II of the dorsal horn. These results suggest that YKS suppresses the development of morphine tolerance by inhibiting the enhancement of presynaptic function of DRG neurons projecting to spinal dorsal horn neurons caused by continuous morphine administration.